Prevalence and associated factors of myopia among school students in Shenyang, China: a cross-sectional study - Zhang, Dan; Sun, Baijun; Wu, Ming; Liu, Huiying; Zhou, Lin; Guo, Lianying (Frontiers in Public Health, 2023)
Background: In recent years, the prevalence of myopia has increased significantly and caused great concern. Nevertheless, an estimate of myopia in the student population in Shenyang, Liaoning Province, China is still lacking. This study aims to determine the prevalence of myopia among students in Shenyang and investigate the associated factors affecting myopia development. Methods: Standard logarithmic visual acuity chart and automatic computerized optometry under non-ciliary muscle paralysis were used to test the students' naked visual acuity of their right and left eyes. The included students were organized to fill in questionnaires on WeChat to collect the factors affecting myopia. Results: A total of 34, 644 students with a median age of 11.9 years were examined, including 17,563 males and 17,081 females. The overall prevalence of myopia was 60%, with a prevalence of 45% for mild myopia, 13% for moderate myopia, and 1.9% for high myopia. The sex, high educational stage, family history of myopia, doing homework after school or reading and writing for more than 2 hours were associated with a higher risk of myopia, while doing eye exercises twice a day or more, going outdoors during recess, reading and writing with eyes more than one foot from books, and sleeping more than 8 hours a day were associated factors for preventing myopia. The associated factors influencing myopia vary among different subgroups. Conclusions: The prevalence of myopia in Shenyang is at a high level. In addition to sex, high educational stage and genetic factors, environmental factors including length of eye usage, eye exercises, outdoor activities, eye working distance, and sleep duration are associated with myopia prevalence. Therefore, it is recommended that the occurrence and development of myopia can be prevented by controlling the above environmental factors.